1989
DOI: 10.1161/01.cir.80.4.873
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound cross-sectional arterial imaging before and after balloon angioplasty in vitro.

Abstract: A prototype ultrasound imaging catheter was evaluated in vitro using 17 human atherosclerotic artery segments before and after balloon dilatation angioplasty. culty in visualizing the coronary tree with a transcutaneous approach.4-6 Recent work has shown that it is feasible to image arteries in cross section using a catheter-mounted ultrasound transducer that generates arterial images from inside the artery lumen.7-9 The purpose of this study was twofold: first, to assess the ability of a newly developed intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(50 citation statements)
references
References 10 publications
0
49
0
1
Order By: Relevance
“…In addition, identification of abnormal tissue components such as atheromatous plaque and calcification have been documented. [1][2][3][4][5] With technologic advances in catheter design, these devices are being applied to study human peripheral and coronary arteries in vivo. 6 -9 Several factors may affect the image quality when this device is used in clinical studies.…”
mentioning
confidence: 99%
“…In addition, identification of abnormal tissue components such as atheromatous plaque and calcification have been documented. [1][2][3][4][5] With technologic advances in catheter design, these devices are being applied to study human peripheral and coronary arteries in vivo. 6 -9 Several factors may affect the image quality when this device is used in clinical studies.…”
mentioning
confidence: 99%
“…Several studies have shown excellent correlations between the lumen cross-sectional area measured from ul- trasound images compared with direct measurements from histologic cross-sections [1,5,6,8,9]. In addition, an in vitro study using acrylamide casts of a phantom model has demonstrated that contrast angiography overestimates the true lumen cross-sectional area compared with intravascular ultrasound when the lumen is not elliptical but irregular experienced interventional angiographers are impressed by the huge amount of residual atheroma that remains at the site of balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanism of balloon angioplasty, intravascular ultrasound imaging was performed in a series of human atherosclerofic arteries in vitro [1] and in human coronary arteries in vivo following balloon dilatation [2]. The purpose of the project was to visualize the morphologic effects of balloon inflation, and to measure the lumen and the atheroma cross-sectional areas at the site of balloon angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports, however, have documented that formalin fixation does not significantly affect the morphology and qualitative echo patterns of plaque tissue. 34,35 Therefore, it can be reasonably extrapolated that the distinct acoustic border between the fibrous cap and the lipid-rich area exists in arterial plaques in vivo as well.…”
Section: Study Limitationsmentioning
confidence: 99%